Medical Imaging 2001: Physics of Medical Imaging 2001
DOI: 10.1117/12.430951
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a-Si:H/CsI flat-panel digital imaging systems with CR-and CCD-based systems: image quality measurements

Abstract: The amorphous silicon/cesium iodide (a-Si:H/CsI:Tl) flat-panel imaging systems have recently become commercially available for both chest and mammographic imaging applications. This new detector technology is considered to be a significant improvement over CR techniques. In this work, we measured the image properties for two commercial flat-panel systems and compared them with those measured for CR and CCD based imaging systems. Image quality measurements related to detector properties such as linearity, MTF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…These digital detectors are based on computed radiography systems (CR), [17][18][19][20][21] charge-coupled devices (CCD), [20][21][22][23][24][25] or amorphous silicon flat-panel systems (FP). 20,21,[26][27][28][29] Computed radiography with storage phosphors was developed in the early 1980's and has been widely used in clinical practice. 3,30 A CR system consists of an image plate (IP) contained in a cassette, compatible with screen/film mammography systems, and an image reader.…”
Section: Introductionmentioning
confidence: 99%
“…These digital detectors are based on computed radiography systems (CR), [17][18][19][20][21] charge-coupled devices (CCD), [20][21][22][23][24][25] or amorphous silicon flat-panel systems (FP). 20,21,[26][27][28][29] Computed radiography with storage phosphors was developed in the early 1980's and has been widely used in clinical practice. 3,30 A CR system consists of an image plate (IP) contained in a cassette, compatible with screen/film mammography systems, and an image reader.…”
Section: Introductionmentioning
confidence: 99%
“…The physical characteristics and performance of this detector have been previously investigated and reported. 3,6,7 The specifications of the slot scanning FFDM system investigated in this study are also listed in Table 1. It employs a CsI(Tl) scintillator coupled to a time-delay integration CCD through fiber-optic tapers for efficient x-ray absorption and integration of the slot scanning exposures.…”
Section: Digital Mammography Systemsmentioning
confidence: 99%
“…Several x-ray detectors have been developed and used in commercial digital mammography systems. They include the storage phosphor plate or computed radiography (CR) imaging plates, [1][2][3] charge-coupled device (CCD) and scintillator based detectors, [3][4][5] and cesium iodide (CsI) or amorphous selenium (a-Se) based flat-panel (FP) detectors. 5-7…”
Section: Digital Mammographymentioning
confidence: 99%
“…The measurements of the modulation transfer function (MTF), noise power spectrum (NPS) and detective quantum efficiency (DQE) of the FP-based and CCD-based systems used in this study were performed in our laboratory previously and reported by Liu et al (2001). The specifications are listed in table 1.…”
Section: Imaging Systemsmentioning
confidence: 99%
“…Currently, screen-film (SF) mammography is still the primary technique used for screening and diagnostic mammography in the United States. In recent years, various digital detectors Rowlands 1997,Pisano et al 2000) have been developed and commercialized for mammography, including computed radiography (CR) systems (Cowen et al 1997,Jenning et al 1996,Kimme-Smith et al 1989,Liu et al 2001,Rong et al 2002, charge-coupled device (CCD)-based systems (Evans et al 2002,Liu et al 2001,Rong et al 2002,Rosen et al 1997,Tesic et al 1999,Vedantham et al 2000b and amorphous silicon flat-panel (FP)-based systems (Liu et al 2001,Mainprize et al 1999,Rong et al 2002,Suryanarayanan et al 2002,Vedantham et al 2000a. These digital detectors use different techniques to improve detective quantum efficiency and to overcome the limitations of conventional SF mammography.…”
Section: Introductionmentioning
confidence: 99%